Association of severe hypoglycemia with depressive symptoms in patients with type 2 diabetes: the Fukuoka Diabetes Registry. Issue 1 (18th May 2015) - Kikuchi, Yohei; Iwase, Masanori; Fujii, Hiroki; Ohkuma, Toshiaki; Kaizu, Shinako; Ide, Hitoshi; Jodai, Tamaki; Idewaki, Yasuhiro; Nakamura, Udai; Kitazono, Takanari
Abstract : Objective: Although many studies have investigated the clinical characteristics of patients with diabetes with depression in Western populations, there is a lack of information regarding other ethnicities. We studied the association between clinical characteristics and depressive symptoms in Japanese patients with type 2 diabetes. Methods: A total of 4218 Japanese patients with type 2 diabetes who were not taking antidepressants were divided into four groups according to the Center for Epidemiologic Studies Depression Scale (CES-D) score. The relationship between the severity of depressive symptoms and clinical parameters was examined cross-sectionally. Results: After multivariate adjustments, the severity of depressive symptoms was significantly associated with body mass index, leisure-time physical activity, current smoking, sleep duration, sucrose intake, skipping breakfast, insulin use, severe hypoglycemia, dysesthesia of both feet, history of foot ulcer, photocoagulation, ischemic heart disease, and stroke. ORs for severe hypoglycemia increased significantly with the CES-D score in 2756 sulfonylurea and/or insulin-treated patients after multivariate adjustment including age, sex, duration of diabetes, glycated hemoglobin, insulin use, self-monitoring of blood glucose, leisure-time physical activity, skipping breakfast, dysesthesia of both feet, ischemic heart disease, and stroke (CES-D score ≤9, referent; 10–15, OR 1.64; 16–23, OR 2.09; ≥24, OR 3.66; p for trend <0.01). Conclusions: Severe hypoglycemia was positively associated with the severity of depressive symptoms in Japanese patients with type 2 diabetes independent of glycemic control, insulin therapy, lifestyle factors, and diabetic complications. As both severe hypoglycemia and depression are known risk factors for morbidity and mortality in patients with diabetes, clinicians should be aware of this association. UMIN Clinical Trial Registry: 000002627.